Teenage first-time mothers' perceptions about their health care needs in the immediate and early postpartum period in Uganda - Mariam Namutebi; Dorcus Kabahinda; Scovia Nalugo Mbalinda; Racheal Nabunya; Dorothy Gingo Nanfuka; Lydia Kabiri; Tom Denis Ngabirano; Patience A. Muwanguzi (BMC, 2022)
Abstract Background Teenagers have higher risks for complications during the intrapartum and postpartum periods. Although facility-based postpartum care focusses on preventing complications in mothers and babies, it is not understood what teenage-mothers' perceptions are about their health care needs in the early postpartum period. Methods An exploratory descriptive qualitative study was conducted in four health facilities in Uganda. In-depth interviews with 42 first-time teenage mothers aged 14 to 19 years were conducted between March and April 2020. Thematic analysis was done. Results Two themes emerged, Health promotion and Rehabilitation and counseling. Teenage first time mothers desired to receive information about key issues like self and newborn care, breast feeding, immunization and family planning. They noted that health workers need to monitor their vital signs which aids in early diagnosis of complications, disease prevention/treatment of current conditions. Others felt that health workers are key in arbitrating between them and their estranged parents and also help to link them to community based organizations that can provide them with counseling and life skills. Conclusions Teenage first-time mothers have many health care needs during the immediate and early postpartum period. This is a missed opportunity to provide health education and link them to sexual reproductive health services including family planning, breastfeeding clinics and other community based programs which provide life skills or continuing education for girls. Focusing on these needs and integration of services is key in providing holistic care to the teenagers. We propose that further research be done to explore how their health care needs change at 6 months post-delivery.